Some New Fractional Inequalities Involving Convex Functions and Generalized Fractional Integral Operator. (21st March 2022) - Neamah, Majid K.; Ibrahim, Alawiah; Mehdy, Hala Shaker; Redhwan, Saleh S.; Abdo, Mohammed S.
Abstract : In this manuscript, we are getting some novel inequalities for convex functions by a new generalized fractional integral operator setting. Our results are established by merging the k, s -Riemann-Liouville fractional integral operator with the generalized Katugampola fractional integral operator. Certain special instances of our main results are considered. The detailed results extend and generalize some of the present results by applying some special values to the parameters.